“Ask the Author”: notes on authorial philology and contemporary playwriting (Altre Modernità, 2020)
Correspondence between the company and the playwright, different versions of the script, rehearsal notes, prompt books: a theatre’s archive can preserve the traces of a creative workshop ideally characterized by an ongoing dialogue, of which the recurring reminder “ask the author” can be a telltale sign. Additions, changes and cuts, in the case of a text intended for performance, are generally negotiated by the writer and other members of the creative team according to their respective style choices, knowledge and needs, so the analysis of the resulting palimpsest can help not only to unveil the story of a single play and to assess the role of variants and variations (when present), but also to reconstruct such complex artistic practices as those of contemporary theatre.In the present paper I mean to illustrate and discuss opportunities and problems of authorial philology applied to contemporary playwriting with particular reference to the new texts produced by Shakespeare’s Globe Theatre and the documents held by its archive.